Harvested populations are more variable only in more variable environments. Issue 12 (24th May 2016) - Cameron, Tom C.; O'Sullivan, Daniel; Reynolds, Alan; Hicks, Joseph P.; Piertney, Stuart B.; Benton, Tim G.
Abstract: The interaction between environmental variation and population dynamics is of major importance, particularly for managed and economically important species, and especially given contemporary changes in climate variability. Recent analyses of exploited animal populations contested whether exploitation or environmental variation has the greatest influence on the stability of population dynamics, with consequences for variation in yield and extinction risk. Theoretical studies however have shown that harvesting can increase or decrease population variability depending on environmental variation, and requested controlled empirical studies to test predictions. Here, we use an invertebrate model species in experimental microcosms to explore the interaction between selective harvesting and environmental variation in food availability in affecting the variability of stage‐structured animal populations over 20 generations. In a constant food environment, harvesting adults had negligible impact on population variability or population size, but in the variable food environments, harvesting adults increased population variability and reduced its size. The impact of harvesting on population variability differed between proportional and threshold harvesting, between randomly and periodically varying environments, and at different points of the time series. Our study suggests that predicting the responses to selective harvesting is sensitive to the demographic structures and processes that emerge in environments with different patterns of environmental variation. Abstract : A number of studies on both terrestrial and aquatic harvested species have suggested that harvesting could increase the temporal variability in population abundance. While this may appear intuitive recent analyses has suggested that environmental variation plays a key role in the responses to harvests and modeled populations show a variety of responses are possible and call for more empirical studies. Here, we show that harvesting of adults does lead to increased temporal population variability, but only in more variable environments.